PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA PEREDARAN OBAT TRADISIONAL YANG MENGANDUNG BAHAN KIMIA OLEH PENYIDIK PEGAWAI NEGERI SIPIL DI BALAI BESAR PENGAWASAN OBAT DAN MAKANAN DI PEKANBARU - Rio Prastio Situmorang; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the social life of modern times not to lose traditional medicine devotees, especially the thought of people who think traditional medicine does not lose quality with medical treatment. This kind of research can be classified into types sosiologis. Riset juridical reseach was conducted in a large hall Pekanbaru food and drug supervision, while the sample population is a whole party with regard to the issues examined in this study. Data sources used, the primary data, secondary data, and the data tertiary data collection techniques in this study with the inteview, and literature study. The authors obtained reseach results can be concluded. Fist, perfom an examination of the report evidence gathering, arrest and detention of offenders while being assisted by the police, conduct an examination of the suspect by investigators BBPOM, manufacture of interrogation, the suspect along with the submission of a letter of introduction from civil servants investigator large hall food and drug oversight to police investigator, submit the results of the investigation to the public prosecutor by police investigators based on book of the law number. 36 of 2009 and coordinate with agencies other law enforcement agencies in solving crime is not rampant circulation of tradisional medicines that contain hazardous chemical materials. The second obstacle faced is the absence of specific legislation governing the crime of trafficking of traditional drugs that contain chemicals either formil or material law from law enforcement factors, such as human resources are still not qualified, insufficient numbers of civil servants hall investigator oversight of exisiting drugs and food, lack of coordination investigator large hall civil servants great hal food and drug surveilllance by law enforcement.Keywords : Implementation Of The Law Enforcement Criminal Offense Circulation Of Traditional Medicine That Contain Harmful Chemicals.